Differentiated, immunobased approach of anaplastic large cell lymphoma treatment in children and adolescents: literature review and protocol ALCL-NII DOG-2003 results - A. S. Volkova; T. T. Valiev (Онкогематология)
Background. Anaplastic large cell lymphoma (ALCL) is a rare variant of highly aggressive lymphomas in children and adolescents. ALCL is characterized by a heterogeneous clinical manifestation with nodal and extranodal lesions, various morphological variants, variable expression of T-cell markers and cytogenetic aberrations involving the ALK gene. Due to the rarity of this disease (up to 10–15 % of all non-Hodgkin’s lymphomas in children), there are no uniform standards for ALCL therapy. Block treatment schemes similar to those applied in the treatment of B-cell non-Hodgkin’s lymphomas are used; less often there can be used protocols similar to the therapy of acute lymphoblastic leukemia. Taking into account the unfavorable effect on the prognosis of T-cell markers expression in ALCL, we developed protocol ALCL-NII DOG-2003, which considered the immunological features of the tumor.Aim. To assess the effectiveness of differentiated immunobased ALCL therapy by domestic protocol ALCL-NII DOG-2003.Materials and methods. From 01.03.1997 to 01.10.2022, 60 patients with primary diagnosed ALCL were included in the study. The diagnosis was based on histological, immunohistochemical and cytogenetic criteria of WHO classification of hematopoietic and lymphoid tissues tumors. According to treatment program, patients were subdivided in 2 groups: patients treated by NHL-BFM 95 protocol (n = 21) and by ALCL-NII DOG-2003 (n = 39). The male:female ratio was 1,3:1 in group of patients with NHL-BFM 95 protocol and 1,4:1 – in ALCL-NII DOG 2003. The effectiveness assessment was based on overall, event-free and relapse-free survival with SPSS 21.0 computed program. The differences between groups were significant with p ≤0.05.Results. The use of risk-adopted, immuno-oriented protocol made it possible to obtain a 10‑year EFS in 97.4 ± 2.6 %, whereas results of the standard NHL-BFM 95 protocol are 63.9 ± 10 % (p = 0.001).Conclusion. The use of a differentiated approach to ALCL treatment, considering not only the stage and prognostic risk group, but also the immunological features of the tumor, is more effective, and allows achieving significantly higher survival rates, than standard program (NHL-BFM 95).